OPTIMIZING THE CARBONIZATION TEMPERATURE OF WATER HYACINTH BIOCHAR BY PROXIMATE ANALYSIS USING RESPONSE SURFACE METHODOLOGY - Maulina, Wenny; Habibah, Putri Sifa; Arkundato, Artoto; Syarifah, Ratna Dewi; Sulistiyo, Yudi Aris; Sukmawati, Nissa (Indonesian Physical Review, 2025)
Water hyacinth is a locally available biomass with the potential to be converted into biochar, serving as a renewable energy source. In this report, response surface methodology (RSM) was employed to optimize the carbonization temperature during the preparation of water hyacinth biochar. Water hyacinth was carbonized in a furnace at varied temperatures (400 °C, 500 °C, 600 °C) for 90 minutes. Characterization of the biochar derived from water hyacinth by proximate analysis was determined, including moisture content, ash content, volatile matter, fixed carbon, and calorific value. The results of the biochar before optimization indicated that moisture content and volatile matter decreased with increasing carbonization temperature, while ash content, fixed carbon, and calorific value increased. After optimization, the proximate analysis of the biochar was determined, with the optimal carbonization temperature found to be 533.54 °C. At this temperature, the optimal moisture content was 6.50%, ash content was 25.53%, volatile matter was 24.80%, and fixed carbon was 43,16%. These findings demonstrate the feasibility of using RSM to optimize the preparation conditions of water hyacinth biochar.